How does regional entrepreneurship transfer over time? The role of household size and economic success - Michael Wyrwich; Michael Fritsch (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
Mounting empirical evidence shows that regional differences of entrepreneurship are persistent over long periods of time that may reflect the prevalence of an entrepreneurial culture. We explore three important mechanisms behind the transmission of such an entrepreneurial culture. First, we analyze the role model effects at the household level. We hypothesize that the larger the households of self-employed, the greater the opportunities for role model effects such as an intergenerational transfer of entrepreneurial values and attitudes, and hence the higher the regional start-up rate in later periods. Second, we investigate how the economic success of regional entrepreneurs fuels the role model effects. Third, we analyze if and to what extent the economic success in of regional entrepreneurship stimulates a collective memory of historical entrepreneurship that spurs self-employment in later periods. The analysis of entrepreneurship in German regions over a period of more than 90 years provides support for the significance of all three transfer channels.
Keywords: L26; R11; O15; J1; 330; Entrepreneurship; intertemporal transfer; regional trajectories